Phase Angle and Impedance Ratio: Reference Cut-Points From the United States National Health and Nutrition Examination Survey 1999–2004 From Bioimpedance Spectroscopy Data. (November 2017) - Kuchnia, Adam J.; Teigen, Levi M.; Cole, Abigail J.; Mulasi, Urvashi; Gonzalez, M. Cristina; Heymsfield, Steven B.; Vock, David M.; Earthman, Carrie P.
Background: Raw bioimpedance parameters (eg, 50-kHz phase angle [PA] and 200-kHz/5-kHz impedance ratio [IR]) have been investigated as predictors of nutrition status and/or clinical outcomes. However, their validity as prognostic measures depends on the availability of appropriate reference data. Using a large and ethnically diverse data set, we aimed to determine if ethnicity influences these measures and provide expanded bioimpedance reference data for the U.S. population. Methods: The National Health and Nutrition Examination Survey (NHANES) is an ongoing compilation of studies conducted by the U.S. Centers for Disease Control and Prevention designed to monitor nutrition status of the U.S. population. The NHANES data sets analyzed were from the years 1999–2000, 2001–2002, and 2003–2004. Results: Multivariate analysis showed that PA and IR differed by body mass index (BMI), age, sex, and ethnicity (n = 6237; R 2 = 41.2%, P < .0001). Suggested reference cut-points for PA stratified by age decade, ethnicity, and sex are provided. Conclusion: Ethnicity is an important variable that should be accounted for when determining population reference values for PA and IR. We have provided sex-, ethnicity-, and age decade–specific reference values from PA for use by future studies in U.S. populations. Interdevice differences are likely to be important contributors to variability across published population-specific reference data and, where possible, should be evaluated in future research. Ultimately, further validation with physiologically relevant reference measures (eg, dual-energy x-ray absorptiometry) is necessary to determine if PA/IR are appropriate bedside tools for the assessment of nutrition status in a clinical population.